PENGEMBANGAN RIKSABASA: APLIKASI PEMERIKSAAN KESALAHAN BERBAHASA INDONESIA - Restu Bias Primandhika; Aurelia Sakti Yani; Adinda Insani Putri; Salman Khairy Farras (Jurnal Semantik, 2023)
Lack of understanding of the General Guidelines for Indonesian Spelling (PUEBI) has an impact on many linguistic errors. For example, in the context of scientific writing written by students, teachers, lecturers or official letters written by an agency both government and private. Based on these problems, this research aims to review existing language applications and develop a user-friendly and effective language checker application called Cekata. The research and development (R&D) method was used in this research. It starts with literature study and data collection to find out the dominance of language errors from various linguistic levels. Then continued with development and testing. Application development is done through prototyping applications such as Adobe XD and development through Android Studio. This research produces an application that is feasible to use for checking errors in writing as well as the initial response of potential users of this application. The response results are as follows: 1) Appearance 87% 2) Main Features 90% 3) User Efficiency 90%.